Automatic VLP’S Recognition For Smart Parking System - Iqbal Munawar; Anisa Rizky; Pajar Rusman (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2022)
The system is designed as the authorized automatic vehicle identifier with respect to vehicle owner identification, for the security of the highly restricted areas like housing areas, defence military areas, parliament areas etc. Both of the number plate recognition and the vehicle owner recognition use the image identification technology. The image of the vehicle plate number and the vehicle owner are captured by using a camera and processed with MATLAB. The system contains an embedded section which controls the opening of the security gate and the communication purpose. The user interface provided at the entry/exit gate gives visual assistance to the driver, whether he/she is not permitted at this area or permitted. The entry of the unauthorized vehicle is restricted and the message is sent to the actual vehicle owner which is preregistered in the systems‟ database. The technology adopted in this research can be utilized not only for the security but also in other fields such as parking fee collection, automatic speed control, tracking stolen cars, automatic toll management and access control to limited areas, etc.